The Influence of English Teacher Certification and Non-Certification towards the Students’ Understanding on English Grammar at SMAN 4 Halmahera Barat and at SMAN 3 Kota Ternate - Mahdi Ahmad; S Sukariman (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2018)
This research used a comparative causal design which was contained test and interview. The objectives of this research are to know could the Teacher certification and non-certification Influence the students understanding on English grammar and to know what problems did the students find when they study English grammar by the Teacher certification and non-certification at that school. The data were collected by using test and interview for the students of that schools. The sample of this research at SMAN 4 HAL-BAR was 22 students and at SMAN 3 Kota Ternate was 21 students of the tenth grade both of the schools. By using grammar material to students who are taught by certified and non-certified teachers in these two schools, namely in SMAN 3 Kota Ternate and at SMAN 4 HAL-BAR the researcher have taken the results of the student evaluation test provided by the two teachers to be able to determine the results of the two schools before being combined with the results of the interview. From the results of this study show that the results of the evaluation of students at SMAN 3 Kota Ternate and combined with the results of the interview, are better than the results of evaluation and interview at SMAN 4 HAL-BAR. In this research, the researcher given conclude to us that the result of teaching grammar through teacher certification at SMAN 3 Kota Ternate is better than students’ result at SMAN 4 HAL-BAR by the teacher of non-certification.